Young adult literature from romance to realism - Cart, Michael; IG Publishing (Chicago American Library Association, 2010)
Today's young adult literature is every bit as complex as the audience it's written for, unflinchingly addressing such topics as homosexuality, mental illness, AIDS and drug abuse. In this much expanded revision of his 1996 book, veteran author Michael Cart shows how the best of contemporary YA lit has evolved to tackle such daunting subjects without resorting to sensationalism. He brings his historical survey of this category fully up to date, covering its explosive growth in the past decade, and advocating that librarians and teachers look beyond romance and horror when advising young adults.
From Sue Barton to the sixties : what's in a name? and other uncertainties -- The sixties and the seventies : the rise of realism and the first golden age -- The eighties : something old, something new : the rise of the paperback series, multicultural literature, and political correctness -- The early nineties : a near-death experience -- The rest of the nineties : revival and renaissance -- A new literature for a new millennium? The renaissance continues -- Romancing the retail : of series, superstores, Harry Potter, and such -- So, how adult is young adult? The crossover conundrum -- Back in the real world : immigration, mixed race, and other new realities of teen life -- Sex and other shibboleths : YA comes of age, and not a moment too soon -- Lesbian, gay, bisexual, and transgender literature : the controversies continue -- The viz biz : transforming the funnies -- The eyes have it : other visual forms : photoessays and the new nonfiction -- Of books and bytes : multiple literacies, the death of print, and other imponderables.
Electronic reproduction.
Keywords: Young adult fiction, American -- History and criticism; Young adult literature -- History and criticism; Teenagers -- Books and reading -- United States; Teenagers in literature; Electronic books